Displays in food retailing: An evaluation from a sales perspective - Lorenz Diederichs; Martin Göbl (Journal of Applied Leadership and Management, 2018)
Purpose: Marketing literature has previously and repeatedly outlined the positive sales effects of displays in food retailing. Therefore, its increasing usage and space allocation is not surprising. Although the promised sales increases of more than 400% should result in even higher usage rates. So the question is if sales and store managers are mismanaging their stores or if a more differentiated evaluation of displays in food retailing necessary. This paper addresses the benefits of displays in food retailing from a holistic perspective, evaluating its overall profitability for stores rather than just sales effects. Additionally it compares displays from a product category's perspective. Design/Methodology: Based on a theoretical approach and a literature review, hypothesis about the profitability of displays overall and for different product categories are derived. A system to evaluate the profitability of displays based on a broad basis of 231 different product placements in more than 30 different stores within the Edeka Handelsgesellschaft Hesserning was developed. The gathered data was finally statistically evaluated and the hypotheses proven. Findings: The profitability of displays depends on a variety of indicators. Displays are far away from being the best option to address most of nowadays retail challenges. Nevertheless, the data indicates the potential of displays for food retailing. Displays hosting impulse goods are most profitable, but a systematic approach throughout the supply chain, involving producers, wholesalers and retailers is necessary, to exploit this full potential. Originality/value: The results are based on more than 3,300 product placements on 231display. The findings and insights are based on a holistic evaluation approach and evaluates the profitability of displays in relation to sales figures, product categories and display characteristics. The findings enable sales and store managers to run retail stores more profitable by simultaneously reducing logistics handling costs and fostering sales. It also helps producers to understand the need to diversify its display offers in order to really generate higher sales volumes.
Keywords: 650; marketing; management; mba; retailing; food retailing; sales; sales management